POLITENESS: CULTURAL DIMENSIONS OF LINGUISTIC CHOICE - Fitriah Fitriah; Didin Nuruddin Hidayat (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
ABSTRACTLanguage has a social function to make connection between human beings. Without language, people seem to be impossible to interact with others in their daily communication. In order to sustain the communication well, speakers should be able to choose strategies to have polite conversation. Often politeness strategies are affected by cultural convention, which is based on community’s social values. However, every society operates a normative notion of their own politeness, which is not the same for all interlocutors, situations and cultures. In Javanese norm, for instance, the linguistic choice is often influenced by the addressee’s age, status, position, relationship, social constraints and gender. This essay will first summarize and comment on some of the salient aspects in Coulmas’ article entitled ‘Politeness: cultural dimension of linguistic choice’, part of his book chapters in ‘Sociolinguistics: The study of speakers’ choices’ (2013). As an English teacher, we should be aware of this difference so that we could introduce the politeness strategies in the target culture to the students.ABSTRAKBahasa memiliki fungsi sosial dalam menjaga hubungan dengan sesama individu. Tanpa bahasa, seseorang tidak akan mampu berinteraksi dengan orang lain dalam komunikasi sehari-hari. Untuk mempertahankan komunikasi dengan baik, pembicara harus dapat memilih strategi yang tepat dalam melakukan percakapan yang sopan. Seringkali norma-norma kesopanan yang ada dipengaruhi oleh konvensi budaya, yang didasarkan dari nilai-nilai social kemasyarakatan. Namun, setiap kelompok masyarakat memiliki nilai kesopanan tersendiri yang didasarkan dari norma kesopanan yang mereka percayai, dan norma kesopanan tersebut tidak sama bagi semua lawan bicara, situasi dan budaya. Dalam norma Jawa, misalnya, pemilihan linguistik atau kata sering dipengaruhi oleh usia, status, posisi, hubungan, pertimbangan sosial dan gender si penerima. Artikel ini akan mengidentifikasi dan mengomentari beberapa aspek yang penting dari tulisannya Coulmas yang berjudul 'Kesopanan: dimensi budaya pilihan linguistik', bagian dari bab dari bukunya Coulmas yang berjudul: 'Sosiolinguistik: Studi tentang pilihan pembicara' (2013). Sebagai guru bahasa Inggris, kita harus menyadari perbedaan penggunaaan kata atau pilihan linguistic sehingga kita bisa memperkenalkan strategi kesopanan dalam budaya tertentu kepada siswa. How to Cite: Fitrah., Hidayat. D. N. (2018). Politeness: Cultural Dimensions of Linguistic Choice. IJEE (Indonesian Journal of English Education), 5(1), 26-34. doi:10.15408/ijee.v5i1.2041